1999
DOI: 10.3758/bf03201219
|View full text |Cite
|
Sign up to set email alerts
|

Shades of the mirror effect: Recognition of faces with and without sunglasses

Abstract: A mirror effect was found for a stimulus manipulation introduced at test. When subjects studied a set of normal faces and then were tested with new and old faces that were normal or wearing sunglasses, the hit rate was higher and the false alarm rate was lower for normal faces. Hit rate differences were reflected in remember and sure recognition responses, whereas differences in false alarm rates were largely seen in know and unsure judgments. In contrast, when subjects studied faces wearing sunglasses, the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
72
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 68 publications
9
72
2
Order By: Relevance
“…When MEMORY, 2006, 14 (1), 79±86 recollection is reduced at testing, the hit advantage is attenuated or reversed, leaving the false alarms untouched. This reduction is also present when the overall results are partitioned as a function of confidence or r-k response categorisation (Hockley, Hemsworth, & Consoli, 1999;Joordens & Hockley, 2000). When pseudowords are not recollectable, due to their novelty, they do not show a mirror pattern.…”
mentioning
confidence: 89%
“…When MEMORY, 2006, 14 (1), 79±86 recollection is reduced at testing, the hit advantage is attenuated or reversed, leaving the false alarms untouched. This reduction is also present when the overall results are partitioned as a function of confidence or r-k response categorisation (Hockley, Hemsworth, & Consoli, 1999;Joordens & Hockley, 2000). When pseudowords are not recollectable, due to their novelty, they do not show a mirror pattern.…”
mentioning
confidence: 89%
“…However, wearing glasses produced fewer matching errors than the no disguise condition (but see Hockley, Hemsworth & Consoli, 1999;Terry, 1994), and these two conditions did not differ from the hat condition (but see Henderson et al, 2001;.…”
Section: Introductionmentioning
confidence: 96%
“…The remember/know response procedure was also used in this experiment. (This study is reported as Experiment 1 by Hockley, Hemsworth, & Consoli, 1999.) The remainder of the interval was occupied in conversation with the experimenter.…”
Section: Methodsmentioning
confidence: 99%